2021
DOI: 10.3390/biom11020298
|View full text |Cite
|
Sign up to set email alerts
|

Nanobodies Provide Insight into the Molecular Mechanisms of the Complement Cascade and Offer New Therapeutic Strategies

Abstract: The complement system is part of the innate immune response, where it provides immediate protection from infectious agents and plays a fundamental role in homeostasis. Complement dysregulation occurs in several diseases, where the tightly regulated proteolytic cascade turns offensive. Prominent examples are atypical hemolytic uremic syndrome, paroxysmal nocturnal hemoglobinuria and Alzheimer’s disease. Therapeutic intervention targeting complement activation may allow treatment of such debilitating diseases. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 133 publications
0
10
0
Order By: Relevance
“…Similar to EWE, the binding mode of S77 results in a steric clash between antibody and MG6 in native C3, which renders the S77 antibody specific for fragments of C3, and the S77 antibody also interferes with FH mediated cleavage of C3b by FI (36). In the context of complement therapeutics, nanobodies and antibodies constitute complementary approaches to dampen excessive activation, with different advantages and disadvantages (reviewed in (20)). One major advantage of EWE is its small size, which readily allowed recombinant fusion to CCP domains of FH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to EWE, the binding mode of S77 results in a steric clash between antibody and MG6 in native C3, which renders the S77 antibody specific for fragments of C3, and the S77 antibody also interferes with FH mediated cleavage of C3b by FI (36). In the context of complement therapeutics, nanobodies and antibodies constitute complementary approaches to dampen excessive activation, with different advantages and disadvantages (reviewed in (20)). One major advantage of EWE is its small size, which readily allowed recombinant fusion to CCP domains of FH.…”
Section: Discussionmentioning
confidence: 99%
“…This binding site of hC3Nb1 inspired us to develop modified nanobodies that does not bind native C3 to allow the nanobody to specifically target sites of complement activation. In this study, we expand our toolbox of complement targeting nanobodies (reviewed in (20)) with the development of a new version of hC3Nb1, called EWE (due to the N-terminal addition of the sequence Glu-Trp-Glu), that specifically binds C3 degradation fragments and inhibits the AP. We present the fusion proteins EWEnH and EWEµH, which comprise EWE fused to either CCP2-4 or CCP2-4 and CCP19-20 of FH, respectively, and restore cofactor activity.…”
Section: Introductionmentioning
confidence: 99%
“…In general, a nanobody is a versatile module that is easily humanized and targeted to specific tissues and cell types by fusion to other proteins. Fusion may also increase the short circulation time of unmodified nanobodies, reviewed in (60). Animal experiments could investigate the in vivo utility of properly modified hCD11bNb1 as a highly specific α M β 2 agonist, but such studies are complicated by the lack of cross-reactivity with the murine αI domain.…”
Section: Function Modulating Molecules Targeting α M βmentioning
confidence: 99%
“…To date, complement-engaging therapeutics are underexplored, and only few therapeutics directly recruit complement to target surfaces. Recently, nanobodies (Nbs) were developed to modulate the complement system (Muyldermans, 2013; Zarantonello et al , 2021). Nbs are derived from the VHH domain of heavy chain-only antibodies found in camelids and composed of a single immunoglobulin domain (Muyldermans, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed that C1qNb75 binds C1q with sub-nanomolar affinity and inhibits activation of the classical pathway (Laursen et al , 2020). Thus, Nbs are proposed as potential novel complement modulators that could offer new therapeutic strategies (Muyldermans, 2013; Zarantonello et al ., 2021) Another study investigated a bispecific antibody, with a Fab binding C1q and another Fab binding to a cell surface target. They showed that the bispecific antibodies were capable of recruiting and activating complement on bacterial surface proteins and B and T cell antigens (Cruz et al , 2019).…”
Section: Introductionmentioning
confidence: 99%